Pre-Induction Scalp Block in a Patient of von Hippel Lindau Disease: Promising Use in High-Risk Neurosurgical Procedures - Anjali Singh; Uma Hariharan; Jyoti Singh; Neerja Banerjee (Research and Practice in Anesthesiology, 2023)
Multiple modalities have been tried for post-craniotomy pain relief, but controversy exists as to the optimal approach. Pre-induction scalp block is a promising technique in high-risk neurosurgical procedures, which reduces the haemodynamic response to skull pin insertion and craniotomy incision, and affords post-operative analgesia. von hippel-lindau (VHL) disease is a rare autosomal dominant disorder with multi-system involvement and various visceral manifestations, the most common of these-being cerebellar hemangioblastoma. Other anomalies include pancreatic-renal cysts, erythrocytosis, hypernephroma, pheochromocytoma and retinal capillary hemangioblastoma. Central nervous system (CNS) hemangioblastomas are often an early manifestation of the disease, and are typically seen in the second decade of life. The majority of hemangioblastomas occur in the cerebellum followed by the spinal cord and brain stem. They are benign vascular tumours but can cause neurological symptoms secondary to pressure or haemorrhage. We hereby present a case of previously diagnosed VHL with recurrent cerebellar hemangioblastoma scheduled for neurosurgical tumour excision and the beneficial use of a pre-induction scalp block to compliment anaesthesia for the patient.